Evaluation of the consequences of early permission of mothers with cesarean delivery - Jalilvand, Faranak; Sadat-Razavi, Maryam; Sharghi, Afshan; Ghavami, Zahra; Izadi, Reza (International Journal of Contemporary Pediatrics, 2021)
Background: In Iran, there is a high tendency to give birth by cesarean section, while about 75% of them are unnecessary and selective. In many hospitals in the country, mothers who have undergone cesarean section are permission 24 hours after the operation if they have stable vital signs and are in good general condition. The aim of this study was to evaluate the consequences of early discharge in mothers who underwent cesarean section. Methods: This descriptive case-series study was performed on 400 pregnant women aged 18-40 years with a gestational age of 37 weeks and more who were admitted to the hospital in Ardabil city for cesarean section at year 2019. Patients without any preference were divided into two groups. The first group was discharged 24 hours and second group was discharged 72 hours after surgery. Individuals in both groups were followed up by telephone 1 and 6 weeks after permission. The relevant checklist was completed for all of them. Other necessary data were collected through a questionnaire containing demographic and clinical information. Results: Two groups were matched in terms of age and body mass index. At one and six weeks after discharge; there was no significant difference between two groups in terms of fever, readmission, symptoms of infection and use of antibiotics. Conclusions: The results of the present study showed that after cesarean section, if the patient’s vital signs are stable, the patient can be discharged after 24 hours.